+0  
 
0
1467
2
avatar

Can you please explain why the following identity is true? Where does it come from: pi/24 = cot^(-1)(2+sqrt(2)+sqrt(3)+sqrt(6)). Thanks for any help.

 Dec 23, 2015

Best Answer 

 #1
avatar+111321 
+15

cot-1( 2 + sqrt(2) + sqrt(3) + sqrt(6) )  = pi/24

 

cot [ pi/24]  = 2 + sqrt(3) + sqrt(2) + sqrt(6)

 

cot [pi/24]  =

                                                              

cot [(1/2)pi/12]] =

 

1/ tan [(1/2)pi/12)] =

 

1/ [sqrt ( 1 - cos(pi/12))/ (1 + cos(pi/12)]  =  

 

sqrt( 1 + cos(pi/12)) / sqrt( 1 - cos(pi/12) ) =  [multiply top/bottom  by sqrt( 1 + cos(pi/12)) ]

 

[1 + cos (pi/12)] / sqrt( 1 - cos^2(pi/12)) =

 

[1 + cos(pi/12)] / sqrt( sin^2(pi/12)) =

 

[1 + cos(pi/12) ] / sin(pi/12)  =

 

1/sin(pi/12) + cos(pi/12) / sin(pi/12)  =

 

 

csc[pi/12] + cot[pi/12] =

 

1/ sin [ pi/12] + 1 / [tan [pi/12]  =

 

1 / [ sin[ pi/4 - pi/6]] + 1 / [ tan[ pi/4 - pi/6] ]

 

1/ [ sin(pi/4)cos(pi/6) - sin(pi/6)cos(pi/4)]  +  1/ ( [tan(pi/4] - tan[pi/6]] / [1 + tan(pi/4)tan(pi/6)] )  =

 

1 / [ sqrt(2)sqrt(3)/4] - (sqrt(2)/4) ] + [ 1 + 1/sqrt(3)]/ [1 - 1/sqrt(3)]  =

 

4 / [ sqrt(6) - sqrt(2)]  +  [ (sqrt(3) + 1)/ sqrt(3))]   / ( [ sqrt(3) - 1]/ sqrt(3) )

 

4 [ sqrt(6) + sqrt(2)]/ 4  +  [ sqrt(3) + 1] / [sqrt(3) - 1]  =  [ multiply the second term by [sqrt(3) + 1] on top/bottom ]

 

sqrt(6) + sqrt(2)  + [sqrt(3) + 1]^2 / 2  =

 

sqrt(6) + sqrt(2) + [3 + 2sqrt(3) + 1] / 2  =

 

sqrt(6) + sqrt(2) + [ 4 + 2 sqrt(3)] / 2  =

 

sqrt(6) + sqrt(2) + 2 + sqrt(3)  =

 

2 + sqrt(3) + sqrt(2) + sqrt(6)    ..........and the left side  =  the right side

 

 

 

cool cool cool

 Dec 23, 2015
edited by CPhill  Dec 23, 2015
edited by CPhill  Dec 23, 2015
edited by CPhill  Dec 23, 2015
 #1
avatar+111321 
+15
Best Answer

cot-1( 2 + sqrt(2) + sqrt(3) + sqrt(6) )  = pi/24

 

cot [ pi/24]  = 2 + sqrt(3) + sqrt(2) + sqrt(6)

 

cot [pi/24]  =

                                                              

cot [(1/2)pi/12]] =

 

1/ tan [(1/2)pi/12)] =

 

1/ [sqrt ( 1 - cos(pi/12))/ (1 + cos(pi/12)]  =  

 

sqrt( 1 + cos(pi/12)) / sqrt( 1 - cos(pi/12) ) =  [multiply top/bottom  by sqrt( 1 + cos(pi/12)) ]

 

[1 + cos (pi/12)] / sqrt( 1 - cos^2(pi/12)) =

 

[1 + cos(pi/12)] / sqrt( sin^2(pi/12)) =

 

[1 + cos(pi/12) ] / sin(pi/12)  =

 

1/sin(pi/12) + cos(pi/12) / sin(pi/12)  =

 

 

csc[pi/12] + cot[pi/12] =

 

1/ sin [ pi/12] + 1 / [tan [pi/12]  =

 

1 / [ sin[ pi/4 - pi/6]] + 1 / [ tan[ pi/4 - pi/6] ]

 

1/ [ sin(pi/4)cos(pi/6) - sin(pi/6)cos(pi/4)]  +  1/ ( [tan(pi/4] - tan[pi/6]] / [1 + tan(pi/4)tan(pi/6)] )  =

 

1 / [ sqrt(2)sqrt(3)/4] - (sqrt(2)/4) ] + [ 1 + 1/sqrt(3)]/ [1 - 1/sqrt(3)]  =

 

4 / [ sqrt(6) - sqrt(2)]  +  [ (sqrt(3) + 1)/ sqrt(3))]   / ( [ sqrt(3) - 1]/ sqrt(3) )

 

4 [ sqrt(6) + sqrt(2)]/ 4  +  [ sqrt(3) + 1] / [sqrt(3) - 1]  =  [ multiply the second term by [sqrt(3) + 1] on top/bottom ]

 

sqrt(6) + sqrt(2)  + [sqrt(3) + 1]^2 / 2  =

 

sqrt(6) + sqrt(2) + [3 + 2sqrt(3) + 1] / 2  =

 

sqrt(6) + sqrt(2) + [ 4 + 2 sqrt(3)] / 2  =

 

sqrt(6) + sqrt(2) + 2 + sqrt(3)  =

 

2 + sqrt(3) + sqrt(2) + sqrt(6)    ..........and the left side  =  the right side

 

 

 

cool cool cool

CPhill Dec 23, 2015
edited by CPhill  Dec 23, 2015
edited by CPhill  Dec 23, 2015
edited by CPhill  Dec 23, 2015
 #2
avatar
0

Thank you CPhill. Brilliant!.

 Dec 23, 2015

14 Online Users

avatar